A mercury-based nitrate second-order nonlinear optical crystal material and its preparation and application

By developing the second -order non -linear optical crystal material A2HG (NO3) 4 of mercury basin nitrate, it solves the problem of insufficient performance of the existing NLO materials in different wavelengths, and achieves a strong multiplier effect and a moderate dual refractive index. Expand the application prospects of materials in the fields of laser frequency conversion.

CN116949575BActive Publication Date: 2025-01-24TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310948893.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-01-24
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

The existing nonlinear optical (NLO) crystal materials have insufficient application performance in different wavelength ranges and have material performance limitations, making it difficult to meet high performance and multifunctional needs.

Method used

Develop a second -order non -linear optical crystal material of mercury basal nitrate. Its chemical formula is A2HG (NO3) 4, of which A is K or RB, which belongs to the square crystal system. Double refractive crystal.

Benefits of technology

This material shows a strong pink frequency effect (9.2 × KDP and 8.8 × KDP), a moderate dual refractive index and short UV -cut border, which is suitable for applications such as laser frequency conversion, and has a broad application prospect in the field of non -linear optics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116949575B_ABST
    Figure CN116949575B_ABST
Patent Text Reader

Abstract

The present invention relates to a mercury-based nitrate second-order nonlinear optical crystal material and its preparation and application. The chemical formula of the crystal material is A 2 Hg(NO 3 ) 4 , wherein A=K or Rb, the molecular weights are 526.83 and 619.57 respectively, belonging to the tetragonal system, the space group is I‑42m (No.121), the unit cell parameters are #imgabs0##imgabs1#α=β=γ=90°, Z=2. The nonlinear optical crystal K of the present invention 2 Hg(NO 3 ) 4 and Rb 2 Hg(NO 3 ) 4 The powder frequency-doubled effects under 1064 nm laser irradiation are approximately KH 2 PO 4 The crystal material has the advantages of wide light transmission band, stable physical and chemical properties, moderate mechanical hardness, and easy growth, and has important application value in the fields of photoelectric conversion such as laser frequency conversion, optical information storage, and electro-optical modulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonlinear optical crystal materials, and relates to a mercury-based nitrate second-order nonlinear optical crystal material and a preparation method and application thereof. Background Art

[0002] As a kind of optoelectronic functional material, nonlinear optical (NLO) crystal materials are widely used in many fields such as laser frequency conversion, laser communication, optoelectronic modulation, laser ranging, medical treatment and national defense and military. With the development of society and the continuous expansion of application fields, the requirements for NLO crystal materials are getting higher and higher. Continuously exploring new NLO materials with better performance and suitable for different wavelength ranges is one of the important tasks and challenges faced by modern scientific researchers. At present, the use of π-conjugated planar triangular structural units (such as [BO3] 3- , [CO3] 2- , [NO3]-) is an effective strategy to develop new NLO materials, such as LiB3O5 (LBO), CsB3O5 (CBO), CsLiB6O 10 (CLBO), β-BaB2O4 (BBO) and KBe2BO3F2 (KBBF) crystals. However, the practical applications of these materials are limited by their inherent shortcomings. Therefore, the development of new high-performance NLO crystal materials is an important research direction in the field of optoelectronic functional materials. Summary of the invention

[0003] The present invention aims to provide a mercury-based nitrate second-order nonlinear optical crystal material and its preparation and application. The crystalline material has a large NLO functional unit density, which is conducive to the generation of a large microscopic polarizability and strong optical anisotropy, and further exhibits a strong powder frequency-doubling effect (9.2×KDP and 8.8×KDP), a moderate birefringence (0.107@532nm and 0.092@532nm) and a short ultraviolet cutoff edge (305nm and 300nm).

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] One of the technical solutions of the present invention provides a mercury-based nitrate second-order nonlinear optical crystal material, whose chemical formula is A2Hg(NO3)4, wherein A=K or Rb, and the crystal material belongs to the tetragonal system, the space group is I-42m, and the unit cell parameters are α=β=γ=90°, Z=2.

[0006] Furthermore, the chemical formula of the crystalline material is K2Hg(NO3)4, which belongs to the tetragonal system, the space group is I-42m, and the unit cell parameters are α=β=γ=90°, Z=2. Further preferably, the unit cell parameters are α=β=γ=90°, Z=2. More preferably, the unit cell parameters are α=β=γ=90°, Z=2. Most preferably, the unit cell parameters are α=β=γ=90°, Z=2.

[0007] The crystal structure of the inorganic compound crystal K2Hg(NO3)4 of the present invention is as follows Figure 1 As shown. Each Hg atom is coordinated with eight oxygen atoms to form a [HgO8] polyhedron. Each [HgO8] polyhedron is connected to four [NO3] groups by edge sharing to form a distorted zero-dimensional [Hg(NO3)4] secondary building unit. They are arranged in the same direction in the crystal structure, which is easy to produce a large frequency-harmonic effect. K atoms are located between adjacent [Hg(NO3)4] units, playing the role of connecting and balancing charges.

[0008] Furthermore, the chemical formula of the crystalline material is Rb2Hg(NO3)4, which belongs to the tetragonal system, the space group is I-42m, and the unit cell parameters are α=β=γ=90°, Z=2. Further preferably, the unit cell parameters are α=β=γ=90°, Z=2. More preferably, the unit cell parameters are α=β=γ=90°, Z=2. Most preferably, the unit cell parameters are α=β=γ=90°, Z=2.

[0009] The crystal structure of the inorganic compound crystal K2Hg(NO3)4 of the present invention is as follows Figure 1 As shown. Each Hg atom is coordinated with eight oxygen atoms to form a [HgO8] polyhedron. Each [HgO8] polyhedron is connected to four [NO3] groups by edge sharing to form a distorted zero-dimensional [Hg(NO3)4] secondary building unit. They are arranged in the same direction in the crystal structure, which is easy to produce a large frequency-doubling effect. Rb atoms are located between adjacent [Hg(NO3)4] units, playing the role of connecting and balancing charges.

[0010] The second technical solution of the present invention provides a method for preparing a mercury-based nitrate second-order nonlinear optical crystal material, which comprises mixing an A source, a Hg source, a N source and water, and continuously stirring until a clear and transparent solution is obtained, and volatilizing at room temperature to obtain a colorless and transparent block crystal, which is the target product.

[0011] Furthermore, the added amounts of A source, Hg source and N source satisfy: the molar ratio of A element, Hg element and N element is (1-10):(1-10):(1-200), preferably (1-10):(1-10):(10-100).

[0012] Furthermore, the volatilization temperature of the solution is 25 to 45° C., more preferably 30 to 35° C., and the volatilization time is not less than one week.

[0013] Furthermore, the A source is nitrate, carbonate, fluoride or chloride of element A.

[0014] Furthermore, the Hg source is mercuric nitrate.

[0015] Furthermore, the N source is nitric acid, or nitrates such as mercuric nitrate.

[0016] A third technical solution of the present invention provides an application of a mercury-based nitrate second-order nonlinear optical crystal material in a laser frequency converter, an optical parametric oscillator, an optical parametric amplifier and a photoelectric rectifier.

[0017] Furthermore, the mercury-based nitrate second-order nonlinear optical crystal material can be used in a laser frequency converter, which can output a 532nm laser under 1064nm laser irradiation.

[0018] Specifically, K2Hg(NO3)4 crystal, as a nonlinear optical crystal material, outputs a strong 532nm laser under 1064nm laser irradiation, and its powder frequency doubling intensity is 9.2 times that of KDP crystal, and can achieve phase matching.

[0019] Specifically, Rb2Hg(NO3)4 crystal, as a nonlinear optical crystal material, outputs a strong 532nm laser under 1064nm laser irradiation, and its powder frequency doubling intensity is 8.8 times that of KDP crystal, and can achieve phase matching.

[0020] The present invention will 10 Transition metal cation Hg 2+ and π-conjugated anion [NO3] - Combined with the above, a quadruple bidentate chelated [Hg(NO3)4] secondary building block was discovered, and the first mercury-based nitrate double-frequency crystal A2Hg(NO3)4 (A=K or Rb) was prepared. The crystalline material has a large NLO functional unit density, which is conducive to the generation of large microscopic polarizability and strong optical anisotropy, and thus exhibits a strong powder double-frequency effect (9.2×KDP and 8.8×KDP), moderate birefringence (0.107@532nm and 0.092@532nm) and short ultraviolet cutoff edge (305nm and 300nm).

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] (1) The present application provides a new second-order nonlinear optical crystal K2Hg(NO3)4, which has a large frequency doubling effect. The frequency doubling intensity is 9.2 times that of KDP crystal under 1064nm laser irradiation, and phase matching can be achieved. In addition, the crystal material has high transmittance in the 310-2500nm spectral range, its ultraviolet absorption cutoff wavelength is 305nm, and its thermal decomposition temperature is 300℃. The crystal material has broad application prospects in the field of nonlinear optics.

[0023] (2) The present application also provides a method for preparing the nonlinear optical crystal K2Hg(NO3)4, and a colorless K2Hg(NO3)4 crystal is prepared by a solution evaporation method. The synthesis method is simple, the synthesis conditions are mild, and it is easy to obtain large-sized single crystals with high optical quality and high purity.

[0024] (3) The present application provides a new second-order nonlinear optical crystal Rb2Hg(NO3)4, which has a large frequency doubling effect. Under 1064nm laser irradiation, the frequency doubling intensity is 8.8 times that of the KDP crystal, and phase matching can be achieved. In addition, the crystal material has a high transmittance in the 310-2500nm spectral range, and its ultraviolet absorption cutoff wavelength is 300nm. The thermal decomposition temperature is 300℃. The crystal material has broad application prospects in the field of nonlinear optics.

[0025] (4) The present application also provides a method for preparing the nonlinear optical crystal Rb2Hg(NO3)4, and a colorless Rb2Hg(NO3)4 crystal is prepared by a solution evaporation method. The synthesis method is simple, the synthesis conditions are mild, and it is easy to obtain large-sized single crystals with high optical quality and high purity. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the crystal structure of K2Hg(NO3)4;

[0027] Figure 2 It is a schematic diagram of the crystal structure of Rb2Hg(NO3)4;

[0028] Figure 3 The X-ray diffraction pattern of sample 1-1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after sample 1-1# is ground into powder;

[0029] Figure 4 The X-ray diffraction pattern of sample 2-1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after sample 2-1# is ground into powder;

[0030] Figure 5 is the UV-Vis-NIR absorption spectrum of sample 1-1#;

[0031] Figure 6 is the UV-Vis-NIR absorption spectrum of sample 2-1#;

[0032] Figure 7 is the infrared spectrum of sample 1-1#;

[0033] Figure 8 is the infrared spectrum of sample 2-1#;

[0034] Fig. 9 This is the thermogravimetric analysis spectrum of sample 1-1#;

[0035] Fig.10 This is the thermogravimetric analysis spectrum of sample 2-1#;

[0036] Fig.11 It is the second harmonic signal diagram of sample 1-1#, sample 2-1# and standard KDP sample with sample size ranging from 105 to 150 μm;

[0037] Fig.12 This is the second harmonic phase matching diagram of sample 1-1# and sample 2-1# in the 1064nm band. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0039] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0040] Embodiment 1:

[0041] Preparation of samples 1# to 8#

[0042] Mix K source, Hg source, N source and water in a certain proportion to form a raw material, place it in a polytetrafluoroethylene beaker and stir it continuously until a clear and transparent solution is obtained. By slowly evaporating at room temperature, colorless and transparent K2Hg(NO3)4 crystals can be obtained.

[0043] The relationship between the type and ratio of raw materials in the initial mixture, the volatilization temperature, the volatilization time and the sample number is shown in Table 1.

[0044] Table 1 Correspondence between samples, raw materials and synthesis conditions

[0045]

[0046] Crystal structure analysis of samples 1# to 8#

[0047] The structures of samples 1-1# to 1-8# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.

[0048] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 298.15K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the Olex2 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.

[0049] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 10-70°, and the scanning step is 0.02°.

[0050] Among them, the single crystal X-ray diffraction results show that samples 1-1#~1-8# have the same chemical formula and crystal structure, the chemical formula is K2Hg(NO3)4, belongs to the tetragonal system, the space group is I-42m, and the unit cell parameters are α=β=γ=90°, Z=2.

[0051] Take sample 1-1# as a typical representative, its crystal structure data is α=β=γ=90°, Z=2. Its crystal structure is as follows Figure 1 shown.

[0052] The powder X-ray diffraction test results show that in the XRD spectra of samples 1-1# to 1-8#, the positions of the diffraction peaks of the samples and the diffraction peaks fitted by the single crystal data are the same, but the peak intensities are slightly different.

[0053] Take sample 1-1# as a typical example. Figure 3As shown, the X-ray diffraction pattern obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is consistent with the peak position and peak intensity of the pattern obtained by X-ray diffraction test after sample 1-1# is ground into powder, indicating that the obtained sample has high purity.

[0054] UV-Vis-NIR absorption spectroscopy test

[0055] The diffuse reflectance absorption spectrum of sample 1-1# was tested on the Agilent Carry 5000 UV-Vis-

[0056] The results were performed on a near-infrared spectrophotometer. Figure 5 As shown by Figure 5 It can be seen that the compound has no absorption peak from 305nm to 2500nm, which proves that the compound has a wide optical transmission range and an optical band gap of 4.06eV.

[0057] Infrared spectrum test

[0058] The infrared spectrum test of sample 1-1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 7 As shown, the characteristic absorption peaks in the infrared spectrum confirm the presence of [NO3] groups in the crystal.

[0059] Thermogravimetric testing

[0060] The thermogravimetric test of sample 1-1# was conducted on a Netzsch STA 409PC thermogravimetric analyzer manufactured by Netzsch Equipment Manufacturing Co., Ltd., Germany. The results are shown in the figure below. Fig. 9 As shown by Fig. 9 It can be seen that the compound can be stable to 300°C and has good thermal stability.

[0061] Frequency doubling test experiment and results

[0062] The frequency doubling test experiment of sample 1-1# is as follows: a Q-switched Nd:YAG solid laser is used to generate a laser with a wavelength of 1064nm and used as the fundamental frequency light to irradiate the tested crystal powder. A photomultiplier tube is used to detect the second harmonic, and an oscilloscope is used to display the harmonic intensity. The crystal sample and the standard sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve. The particle size ranges are 26-50, 50-74, 74-105, 105-150, 150-200, and 200-280μm. Observe the change law of the frequency doubling signal with the particle size to determine whether it can achieve phase matching. Under the same test conditions, the second harmonic intensity generated by the sample and the standard sample KDP is compared to obtain the relative size of the sample frequency doubling effect.

[0063] The test results show that the compound K2Hg(NO3)4 has a large powder frequency-doubled effect. Under 1064nm wavelength laser irradiation, the frequency-doubled signal intensity is 9.2 times that of KDP crystal (such as Fig.11 ). The crystal material can achieve phase matching under 1064nm laser irradiation (such as Fig.12 ).

[0064] Example 2

[0065] Preparation of samples 1# to 8#

[0066] Rb source, Hg source, N source and water are mixed into a raw material in a certain proportion, placed in a polytetrafluoroethylene beaker and stirred continuously until a clear and transparent solution is obtained. Colorless and transparent Rb2Hg(NO3)4 crystals can be obtained by slowly evaporating at room temperature.

[0067] The relationship between the type and ratio of raw materials in the initial mixture, the volatilization temperature, the volatilization time and the sample number is shown in Table 2.

[0068] Table 2 Correspondence between samples and raw materials and synthesis conditions

[0069]

[0070]

[0071] Crystal structure analysis of samples 1# to 8#

[0072] The structures of samples 2-1# to 2-8# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.

[0073] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 298.15K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the Olex2 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.

[0074] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 10-70°, and the scanning step is 0.02°.

[0075] Among them, the single crystal X-ray diffraction results show that samples 2-1#~2-8# have the same chemical formula and crystal structure, the chemical formula is Rb2Hg(NO3)4, belongs to the tetragonal system, the space group is I-42m, and the unit cell parameters are α=β=γ=90°, Z=2.

[0076] Take sample 1-1# as a typical representative, its crystal structure data is α=β=γ=90°, Z=2. Its crystal structure is as follows Figure 2 shown.

[0077] The powder X-ray diffraction test results show that in the XRD spectra of samples 2-1# to 2-8#, the positions of the diffraction peaks of the samples and the diffraction peaks fitted by the single crystal data are the same, but the peak intensities are slightly different.

[0078] Take sample 2-1# as a typical example. Figure 4 As shown, the X-ray diffraction pattern obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is consistent with the peak position and peak intensity of the pattern obtained by X-ray diffraction test after sample 2-1# is ground into powder, indicating that the obtained sample has high purity.

[0079] UV-Vis-NIR absorption spectroscopy test

[0080] The diffuse reflectance absorption spectrum of sample 2-1# was tested on the Agilent Carry 5000 UV-Vis-

[0081] The results were performed on a near-infrared spectrophotometer. Figure 6 As shown by Figure 6 It can be seen that the compound has no obvious absorption from 310nm to 2500nm, which proves that the compound has a wide optical transmission range and an optical band gap of 4.13eV.

[0082] Infrared spectrum test

[0083] The infrared spectrum test of sample 2-1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 8 As shown, the characteristic absorption peaks in the infrared spectrum confirm the presence of [NO3] groups in the crystal.

[0084] Thermogravimetric testing

[0085] The thermogravimetric test of sample 2-1# was conducted on a Netzsch STA 409PC thermogravimetric analyzer manufactured by German Netzsch Equipment Manufacturing Co., Ltd. The results are shown in the figure below. Fig.10 As shown by Fig.10 It can be seen that the compound can be stable to 300°C and has good thermal stability.

[0086] Frequency doubling test experiment and results

[0087] The frequency doubling test experiment of sample 2-1# is as follows: a Q-switched Nd:YAG solid laser is used to generate a laser with a wavelength of 1064nm and used as the fundamental frequency light to irradiate the tested crystal powder. A photomultiplier tube is used to detect the second harmonic, and an oscilloscope is used to display the harmonic intensity. The crystal sample and the standard sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve. The particle size ranges are 26-50, 50-74, 74-105, 105-150, 150-200, and 200-280μm. Observe the change law of the frequency doubling signal with the particle size to determine whether it can achieve phase matching. Under the same test conditions, the second harmonic intensity generated by the sample and the standard sample KDP is compared to obtain the relative size of the sample frequency doubling effect.

[0088] The test results show that the compound Rb2Hg(NO3)4 has a large powder frequency-doubled effect. Under 1064nm wavelength laser irradiation, the frequency-doubled signal intensity is 8.8 times that of KDP crystal (such as Fig.11 ). The crystal material can achieve phase matching under 1064nm laser irradiation (such as Fig.12 ).

[0089] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A mercury-based nitrate second-order nonlinear optical crystal material, characterized in that: Its chemical formula is A2Hg(NO3)4, where A=K or Rb. The crystal material belongs to the tetragonal system, the space group is I-42m, and the unit cell parameters are α=β=γ=90°, Z=2.

2. The mercury-based nitrate second-order nonlinear optical crystal material according to claim 1, characterized in that: The chemical formula of the crystalline material is K2Hg(NO3)4, which belongs to the tetragonal system, the space group is I-42m, and the unit cell parameters are α=β=γ=90°, Z=2; Or the chemical formula of the crystalline material is Rb2Hg(NO3)4, which belongs to the tetragonal system, the space group is I-42m, and the unit cell parameters are α=β=γ=90°, Z=2.

3. The method for preparing a mercury-based nitrate second-order nonlinear optical crystal material according to claim 1 or 2, characterized in that: Mix the A source, Hg source, N source and water and stir continuously until a clear and transparent solution is obtained. After volatilization at room temperature, colorless and transparent crystals are obtained, which are the target product.

4. The method for preparing a mercury-based nitrate second-order nonlinear optical crystal material according to claim 3, characterized in that: The added amounts of A source, Hg source and N source satisfy: the molar ratio of A element, Hg element and N element is (1-10):(1-10):(1-200).

5. The method for preparing a mercury-based nitrate second-order nonlinear optical crystal material according to claim 3, characterized in that: The evaporation temperature of the solution is 25-45°C, and the evaporation time is not less than one week.

6. The method for preparing a mercury-based nitrate second-order nonlinear optical crystal material according to claim 3, characterized in that: The A source is nitrate, carbonate, fluoride, and chloride containing the A element.

7. The method for preparing a mercury-based nitrate second-order nonlinear optical crystal material according to claim 3, characterized in that: The Hg source is mercuric nitrate.

8. The method for preparing a mercury-based nitrate second-order nonlinear optical crystal material according to claim 3, characterized in that: The N source is nitric acid or nitrate.

9. Use of a mercury-based nitrate second-order nonlinear optical crystal material as claimed in claim 1 or 2 in a laser frequency converter, an optical parametric oscillator, an optical parametric amplifier and a photoelectric rectifier.

10. The use of a mercury-based nitrate second-order nonlinear optical crystal material according to claim 9, characterized in that: Mercury-based nitrate second-order nonlinear optical crystal material is used in laser frequency converters and can output 532nm laser under 1064nm laser irradiation.

Citation Information

Patent Citations

  • Bi3TeO6OH(NO3)2 compound, Bi3TeO6OH(NO3)2 nonlinear optical crystal, and preparation method and applications of Bi3TeO6OH(NO3)2 compound and Bi3TeO6OH(NO3)2 nonlinear optical crystal

    CN106542505A

  • Guanidine tetrafluoroborate nonlinear optical crystal and preparation method and application thereof

    CN112760717A